Relationships between muscle electrical activity and the control of inter-vertebral motion during a forward bending task. (December 2018) - du Rose, Alister; Breen, Alex; Breen, Alan
Abstract: Muscle strengthening exercises are commonly used in primary care for the treatment of chronic, non-specific low back pain (CNSLBP) as it has been theorised that increased muscle activity contributes to the stabilisation of inter-vertebral motion segments during bending and other spinal movements, however this has never been demonstrated in vivo . This study used contemporaneous quantitative fluoroscopy (QF) and surface electromyography (sEMG) to investigate relationships between continuous inter-vertebral motion variables and muscle electrical activity in the lumbar multifidus (LMU), lumbar and thoracic erector spinae (LES and TES) during standardised lumbar flexion and return in 18 healthy male human subjects. Our results demonstrated that the variability in the sharing of angular motion (i.e. Motion Share Variability MSV) and motion segment laxity during a bending task were significantly (p < 0.05) negatively correlated (Spearman) with muscle electrical activity throughout the participant bend for both locally and globally acting muscle groups. MSV was also strongly correlated with L2-3 laxity. The former suggests a damping mechanism reducing irregular displacements (i.e. less variability in the sharing of segmental motion) during bending and an action of spinal stabilisation by muscles at segmental levels, and the latter a synergy between laxity at L2-3 and MSV. While this has previously been theorised, it has never been shown in vivo at the inter-vertebral level. These assessments may be considered for use in validation studies of exercise programs for CNSLBP, however further replication is required.